Analyzing the Impact of Audiovisual Media in Islamic Religious Education and Character Education to Enhance Students' Learning Interest - mahbubi, Muhammad; Tohet, Moch; Diadara, Eva (Electronic Journal of Education, Social Economics and Technology, 2024)
This article discusses the impact of audiovisual analysis in learning Islamic Religious Education and Ethics to foster interest in learning students SMP Negeri 1 Leces. The purpose of this study was to determine the impact of the application of audiovisual in learning, especially the subjects of Islamic Religious Education and Ethics. Widely known in the field of technology media use in Indonesia, its development is very rapid, so that not a few schools that take advantage of the speed of technological development as a medium of learning, one of which is in Islamic Religious Education and character. The type of research used in this study is qualitative with a case study approach through interviews and literature studies, analyzing the impact of audiovisual in learning Islamic Religious Education and Ethics, both positive and negative factors. This is motivated by the presence of some students who use technology media not only for the sake of learning, but many things that can be accessed easily about what they want. So that it changes the understanding and learning interest of students in Islamic Religious Education teaching materials and character, both academic ability and personality